MENATAP PUTARAN KEDUA PEMILIHAN KEPALA DAERAH (PILKADA) DI DAERAH KHUSUS IBU KOTA JAKARTA TAHUN 2017 - Dwi Andayani Budisetyowati (Era Hukum - Jurnal Ilmiah Ilmu Hukum, 2017)
As stated under Article 18 of Indonesian Constitution, Indonesia is separated into provinces and those provinces are separated into districts and cities, on which every province, district, and city is managed by respective local government as regulated by Law of Indonesia No. 23/2014 concerning Local Government. Province, district and city manage and take care of their own local governmental issues in accordance with autonomy and delegation principle. As an autonomy area, province, district and town have local government to enforce governmental functions, which are Local Government and Local House of Representative. The local head of district is the local head of district in province, district or city area, who serves as the area executive body and its Local House of Representative. Both are the government’s enforcing elements. . The 2017 Local Election was held simultaneously by 101 areas consist of provinces, districts, and cities. The election has just done on 15 February 2017.  The writer creates this writing by taking the election in DKI Jakarta as an example, considering the fact that DKI Jakarta is a privileged province in enforcing local government due to its capacity as the capital city of Indonesia. Keywords:  Local Government Election, Second Round, Special Capital Region of Jakarta